National belonging post‐referendum: Britons living in other EU Member States respond to "Brexit". Issue 2 (23rd July 2018) - Higgins, Katie W.
Abstract : Following the EU Referendum, this paper tracks how pro‐Remain British migrants living in other EU Member States expressed a sense of shame and dislocation in relation to their national identity. Developed from a survey of 909 British nationals living in other EU Member States, it hopes to make a timely intervention into wider debates about privileged migration, Britishness, citizenship and belonging. First, it outlines a new articulation of the "bad Britain" discourse among emigrants, who saw the UK as increasingly characterised by xenophobia and insularity. Second, it seeks to understand how their national identity and sense of belonging was being renegotiated post‐referendum through a lens attentive to the cultural politics of emotion and innocence as an operation of whiteness. Abstract : Following the EU Referendum, this paper tracks how pro‐Remain British migrants living in other EU Member States expressed a sense of shame and dislocation in relation to their national identity. Developed from a survey of 909 British nationals living in other EU Member States, it hopes to make a timely intervention into wider debates about privileged migration, Britishness, citizenship and belonging. First, it outlines a new articulation of the "bad Britain" discourse among emigrants, who saw the UK as increasingly characterised by xenophobia and insularity. Second, it seeks to understand how their national identity and sense of belonging was being renegotiated post‐referendum through a lens attentive to the cultural politics of emotion and innocence as an operation of whiteness.